Perencanaan Bisnis Naturcase - Syifa, Nur Amira; Betari, Betari Suwandi; Ghina Tsuraya, Klara Ningrum; Wardani, Nira Kusuma; Deana Ismail, Tasyara; Hapsari, Karina Tiara; Juwanda, Vidella; Suwandi, Dr (Journal of Entrepreneurship, Management and Industry (JEMI), 2020)
The purposes of this analysis of business concept and functions are: 1) The business concept of Naturcase, 2) Naturcase products, 3) Market strategies for Naturcase’s products in order to be better known by the public and increase the sales. The analysis tools are: SWOT Analysis, STP Analysis, and Financial Analysis. The Business plan of Naturcase itself projects a payback period for 1 year 6 months, so it can be concluded that the business plan are profitable and feasible to run.   Keywords: Business Plan, Naturcase, SWOT Analysis, STP Analysis, Payback Period